Genetic diversity of primate strongylid nematodes: Do sympatric nonhuman primates and humans share their strongylid worms? - Pafčo, Barbora; Kreisinger, Jakub; Čížková, Dagmar; Pšenková-Profousová, Ilona; Shutt-Phillips, Kathryn; Todd, Angelique; Fuh, Terence; Petrželková, Klára J; Modrý, David (Molecular ecology, 2019)
The close phylogenetic relationship between humans and nonhuman primates (NHPs) can result in a high potential for pathogen exchange. In recent decades, NHP and human interactions have become more frequent due to increasing habitat encroachment and ecotourism. Strongylid communities, which include members of several genera, are typically found in NHPs. Using optimized high-throughput sequencing for strain-level identification of primate strongylids, we studied the structure of strongylid communities in NHPs and humans co-habiting a tropical forest ecosystem in the Central African Republic. General taxonomic assignment of 85 ITS-2 haplotypes indicated that the studied primates harbour at least nine genera of strongylid nematodes, with Oesophagostomum and Necator being the most prevalent. We detected both host-specific and shared strongylid haplotypes. Skin-penetrating Necator gorillaehaplotypes were shared between humans and gorillas but Necator americanus were much more restricted to humans. Strongylid communities of local hunter-gatherers employed as trackers were more similar to those of gorillas compared to their relatives, who spent more time in villages. This was due to lower abundance of human-origin N. americanus in both gorillas and trackers. Habituated gorillas or those under habituation did not show larger overlap of strongylids with humans compared to unhabituated. We concluded that the occurrence of the human-specific strongylids in gorillas does not increase with direct contact between gorillas and humans due to the habituation. Overall, our results indicate that the degree of habitat sharing between hosts, together with mode of parasite transmission, are important factors for parasite spillover among primates.
Keywords: sympatrie; Sympatry; Animals; ekosystém; Genetic Variation; Humans; Ecosystem; Phylogeny; Primates; lidé; Gorilla gorilla; zvířata; primáti; fylogeneze; genetická variace; Oesophagostomum; Necator